Análisis de las diferentes opciones para la elaboración de un biopolímero utilizando lactosuero como materia prima. (2022)
The main objective of this document is to analyze the different options for the production of a biopolymer using cheese whey as a substrate, in order to reduce the environmental impact that it generates when it is dumped into the environment and additionally generate an alternative to common plastics of fossil origin. Initially, a bibliographical review of the different physicochemical and microbiological properties of chesee whey was carried out, identifying that many of these properties can vary according to the cheese making process, its origin, livestock feeding, among other factors.